2016
DOI: 10.7314/apjcp.2016.17.4.1725
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Del 185 AG and 4627C>A BRCA1 Mutations in Breast Cancer Patients from Lahore, Pakistan

Abstract: Breast cancer contributes to approximately 23% of the cancer cases identified and 14% of cancer related deaths worldwide. Including a strong association between genetic and environmental factors, breast cancer is a complex and multi factorial disorder. Two high penetration breast cancer susceptibility genes (BRCA1 and BRCA2) have been identified, and germ line mutations in these are thought to account for between 5% and 10% of all breast cancer cases. The human BRCA1 gene, located on 17q, is involved in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
2
1
Order By: Relevance
“…The founder mutations are expected in consanguineous populations like the present one. Although we did not find any recurrent mutation in the present cohort, comparison with previously published reports indicated that 185delAG may be a founder mutation ( Liede et al, 2002 ; Rashid et al, 2006 ; Moatter et al, 2011 ; Ahmad et al, 2012 ; Aziz et al, 2016 ; Rashid et al, 2016 ; Rashid et al, 2017 ; Torres et al, 2017 ).…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The founder mutations are expected in consanguineous populations like the present one. Although we did not find any recurrent mutation in the present cohort, comparison with previously published reports indicated that 185delAG may be a founder mutation ( Liede et al, 2002 ; Rashid et al, 2006 ; Moatter et al, 2011 ; Ahmad et al, 2012 ; Aziz et al, 2016 ; Rashid et al, 2016 ; Rashid et al, 2017 ; Torres et al, 2017 ).…”
Section: Discussioncontrasting
confidence: 75%
“…In Pakistani population, some studies have analyzed BRCA1 and BRCA2 mutations ( Liede et al, 2002 ; Rashid et al, 2006 ; Moatter et al, 2011 ; Ahmad et al, 2012 ; Aziz et al, 2016 ; Rashid et al, 2016 ; Rashid et al, 2017 ; Torres et al, 2017 ), mainly through conventional methodologies. In case of other putative breast cancer susceptibility genes, scarce or no data is available from this region ( Khaliq et al, 2000 ; Baig et al, 2011 ; Rashid et al, 2014 ; Baloch et al, 2016 ; Rashid et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding family history, patient in present study reported to have negative family history for any kind of cancer as Liede et al , 2002 16 also reported the victims with this mutation had negative family history for such cancers. Previous studies on Pakistani population also tried to find relation with ethnicity as Rashid et al, 2006 17 reported BRCA1 - 185 Del AG in two of the pathan patients while Liede et al , 2006 16 and Aziz et al , 2016 18 reported this mutation in patient with Punjabi ethnicity and currently it was also observed in patient with Punjabi ethnicity. In the two prior studies on Pakistani population that included exon-2 in investigation none of the patients found to be positive for 185 delAG .…”
Section: Discussionmentioning
confidence: 99%